F(x) = x² + 4x - 12
x = -b/2a
x = -(4)/2(1)
x = -4/2
x = 2
f(x) = x² + 4x - 12
f(2) = (2)² + 4(2) - 12
f(2) = 4 + 8 - 12
f(2) = 12 - 12
f(2) = 0
The vertex of the function is (2,0).
Answer:
3 Chapters?
Step-by-step explanation:
3x1=3 but I am not sure if it is asking if you read during school or not because this seems like a really simple question and may be over thinking it.
The magnitude of each vector is the Pythagorean sum of its components.
a. |v1| = √(2² + (-6)²) = √40 = 2√10
|v2| = √((-4)² + 7²) = √65
b. To make each vector into a unit vector, divide each component by the vector's magnitude.
u1 = v1/|v1| = (2/(2√10), -6/(2√10))
u1 = (√10/10, -3√10/10)
u2 = v2/|v2| = (-4/√65, 7/√65)
u2 = (-4√65/65, 7√65/65)
Writing this word problem symbolically: 6x + 4 = x = 11.
Combining like terms, 5x = 7, and so x = 7/5 (answer)
We know that
surface area=area of the base+4*[area of one lateral triangle side]
area of the base=b²
b is the side length of the square
b=14 cm
area of the base=14²-----> 196 cm²
area of one lateral triangle side=b*h/2
b is the side length of the square
b=14 cm
h is the height of the lateral triangle side
h is equal to the slant height
h=15 cm
area of one lateral triangle side=14*15/2----> 105 cm²
surface area=196+4*[105]------> 616 cm²
the answer is
the surface area is 616 cm²